(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Mahasweta has composed hundred books surprisingly, including books, plays and gathering of stories. She has won the renowned Jnanpith and Magasasay Awards for writing is worried about the predicament of the tribals living on the periphery. Mahasweta turns out to be increasingly more engaged with the lives and battles of the unprivileged ancestral ladies and the barbarities incurred on them. Draupadi is about the Santhal clan young lady, who is powerless against foul play yet oppose the copied of social persecution and viciousness with unstoppable will and mental fortitude and even attempt to deconstruct the well established structures of racial and sex segregation. Draupadi is interpreted by Gayatri Chakravorty Spivak. The most fascinating piece of the story is that Dopdi Mejhen is depicted as an unskilled, uneducated innate lady. However she drives the politicized life among all since she is occupied with an equipped battle for the rights and opportunity of the innate individuals. This paper gives the advanced breaks custom and the improvement of new types of talk and agreeable with the ladies’ motivation for the issues that in dismissing the double structures of male centric talks which are sight of the political, social and ideological powers of bigotry in our general public.